ERROR ANALYSIS OF CONCORD USAGE IN ABSTRACTS OF INDONESIAN ENGLISH JOURNAL ARTICLES - Anggelina Sri Saparti Sitompul; Maria Dewi Rosari (PROJECT (Professional Journal of English Education), 2024)
This research aims to find out the types of concord (Roy, 2019) that are violated in abstracts of Indonesian English SINTA-6-accredited journal articles and in which the types of errors by Dulay et al. (1982) those violated concord fall. A qualitative method was used for researching the incorrect use of concord. In conducting document analysis, this research utilized checklist tables as the instruments. The researchers collected the data from 108 abstracts. After collecting, validating, and analyzing, the researchers found 74 occurrences of violated concord in 47 article abstracts, all of which were grammatical concord as the most frequently violated. Those violated grammatical concord fell into three types of errors, namely omission, misformation, and addition out of four, where omission was the most frequently committed. Misformation errors had slightly different occurrences with omission, amounting to 7 occurrences. Those two findings showed that the authors of the articles were struggling with them. Hence, it is hoped through this research, authors and editorial teams of Indonesian English journal articles be more alert to the potential errors in concord usage in the research articles produced to be able to produce and publish more quality research papers.